2023
DOI: 10.3126/qjmss.v5i1.56291
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomics as the Basis of Commercial Banks Stability in Nepal

Abstract: Background:  Maintaining financial stability is vital for all financial institutions, as it fosters public trust and confidence in the entire system contributing to a healthy and well-operating economy in a country. Therefore, banks and other financial institutions must uphold their financial soundness and stability, given their crucial economic role. Objective:  The study examines the influence of macroeconomic factors such as Inflation (INF), Gross Domestic Product (GDP) growth, Inflation Rate (INF), the Exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, they found that the inflation had a negative link with profitability. By processing time series data of 22 years on cointegration test and an error correction model, Gwachha and Karmacharya (2023) found significant negative impact of inflation on bank stability in Nepal. Acharya and Vyas (2022) also found negative impact of inflation on Nepalese banks' profitability.…”
Section: Credit Risk External Factors and Profit Of Banksmentioning
confidence: 99%
“…However, they found that the inflation had a negative link with profitability. By processing time series data of 22 years on cointegration test and an error correction model, Gwachha and Karmacharya (2023) found significant negative impact of inflation on bank stability in Nepal. Acharya and Vyas (2022) also found negative impact of inflation on Nepalese banks' profitability.…”
Section: Credit Risk External Factors and Profit Of Banksmentioning
confidence: 99%